In vitro antimicrobial activity of different electrochemicallyactivated solutions on enterococcus faecalis - Makbule Bilge Akbulut; Ayçe Ünverdi Eldeniz (European Oral Research)
PurposeThe aim of this in vitro study was to assess and compare the antimicrobial efficacy of different electrochemically-activated solutions (ECA) and contemporary irrigants, in root canals infected with Enterococcus faecalis, used with or without EndoActivator (EA).Materials and methodsA hundred single-rooted human teeth were prepared. Ninety of the root segments were infected with E. faecalis for four weeks, and divided into eight test groups (n = 10) (four with and four without EA sonication) and a positive control (n = 10). The irrigants tested were electrochemically-activated solutions produced by the Medilox® (ECA-MX) and Envirolyte® devices (ECA-EN), 2% CHX and 2.5% NaOCl. The root specimens were irrigated with 5 mL of the test solution, with additional sonic agitation applied to the EA groups. The dentine samples that were obtained from the walls were cultured, and the antibacterial efficacy was evaluated by counting the colony-forming units.ResultsThe ECA-EN, 2.5% NaOCl and 2% CHX were more effective than the ECA-MX (p <0.05) with the addition of EA sonication, showing no statistical difference in the elimination of E. faecalis.ConclusionThe ECA-EN shows potential as an endodontic irrigant, while EA usage gives no benefit in reducing bacteria from root canals.